Love, Rosie - Ahern, Cecelia, 1981- (New York : Hyperion, 2005)
Rosie and Alex have been best friends since childhood, so when Alex's family moves from Dublin to Boston, Rosie decides she'll venture to the States for college after she graduates from high school. But those dreams are dashed when the night of her final high-school dance leaves Rosie pregnant. She decides to stay in Dublin and keep the baby. When Rosie comes over to visit Alex during his last year at Harvard, she finds herself falling for him--just as he announces his engagement to a fellow student. Thus begins a back-and-forth that goes on for years, as Rosie raises her daughter and pursues her dream job while Alex builds a life for himself in Boston.
Keywords: Love stories; Humorous fiction